Dampak Kebijakan Pemerintahan Orde Baru dan Perubahan Sosial Terhadap Perkembangan Pendidikan Anak Tahanan G30S di Pulau Buru 1969-1976 - Chusata, Rimadany Yuda (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the impact of New Order government policies on the educational development of children of G30S prisoners on Buru Island in the 1969-1976 period. During that time, the New Order government in Indonesia implemented various policies that influenced various aspects of life, including the education of children of G30S prisoners on Buru Island. This research reviews these policies and tries to identify their impact on children's education